2019
DOI: 10.1155/2019/5636528
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element- and Design of Experiment-Derived Optimization of Screw Configurations and a Locking Plate for Internal Fixation System

Abstract: Objectives. The optimization for the screw configurations and bone plate parameters was studied to improve the biomechanical performances such as reliable internal fixation and beneficial callus growth for the clinical treatment of femoral shaft fracture. Methods. The finite element analysis (FEA) of internal fixation system under different screw configurations based on the orthogonal design was performed and so was for the different structural parameters of the locking plate based on the combination of unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Our finding also corroborated the result of, 16 which studied the risk of implant failure and argued against the placement of screws close to the fracture site. With regard to the present results for the optimal screw diameter ( D = 5.5 mm), LCP thickness ( T = 4 mm), and plate width ( W = 12 mm), it is encouraging to compare our findings with those found by another study, 55 which resulted in 5 mm, 4.6 mm, and 11 mm, as optimal values for D , T , and W , respectively. Although the findings of the study by Sheng and coworkers were determined through an optimization scheme, the criteria used for evaluating the optimal performance of LCP were limited to the stress in the internal fixation construct and interfragmentary strain in callus, which was less general and simpler than our study.…”
Section: Discussionsupporting
confidence: 84%
“…Our finding also corroborated the result of, 16 which studied the risk of implant failure and argued against the placement of screws close to the fracture site. With regard to the present results for the optimal screw diameter ( D = 5.5 mm), LCP thickness ( T = 4 mm), and plate width ( W = 12 mm), it is encouraging to compare our findings with those found by another study, 55 which resulted in 5 mm, 4.6 mm, and 11 mm, as optimal values for D , T , and W , respectively. Although the findings of the study by Sheng and coworkers were determined through an optimization scheme, the criteria used for evaluating the optimal performance of LCP were limited to the stress in the internal fixation construct and interfragmentary strain in callus, which was less general and simpler than our study.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, Sheng and co-workers used experimentally validated FE models, without modeling tissue differentiation at the fracture gap, and found the optimal thickness of 4.6 mm for the internal fixation of femoral mid-shaft fracture, fixed by an 10-holes LCP, using a comprehensive optimization process for the LCP system. 44…”
Section: Discussionmentioning
confidence: 99%
“…The location and configuration of the screws in the plate is another important parameter in plate and screw osteosynthesis. In a study they conducted, Wei Sheng et al [13] found that the stress loads on the plate in nine different plate screw configurations of the same length were similar. They also found that the stress on the plate and femur increased significantly in the first and second screw holes near the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Screw diameter also plays an important role in the mechanics of internal fixation [28,29]. In their study comparing the screw diameters of 4 mm, 4.5 mm, 5 mm, Wei Sheng et al [13] revealed that the highest stress on the plate was on the 4 mm screws. They showed that the most suitable screws were those with 5mm diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation